(untitled) (Journal of Bio-Science, 2011)
Context: Diatomaceous earth (DE) compounds have been recognized as reduced risk and eco-friendly compounds, which can be used in the insect pest management programmes for food storage and processing areas. Objective: To determine the repellent or attractant property of a DE formulation (Mitex) against the larvae of Tribolium castaneum (Herbst), a major pest of stored-products. Materials and Methods: The experiment was conducted in choice chambers, which was divided into two equal halves by drawing a line through the midline. One half of the chamber was loaded with untreated flour (control) and the other half was loaded with DE-treated flour. Twenty larvae of a definite age were released in the midline of the two foods, thus providing them an option for choosing either treated or untreated food. The experiment was set separately for different ages of larvae (9-, 12- and 15-day old), doses of DE (2, 4, 8, 16 and 32 mg DE/g of flour) and exposure periods (24-, 48-, 72-, 96- and 120-hours). All the experiments were replicated three times and conducted at 30 ± 1°C in an incubator without humidity and light control. Differences of the distribution of the larvae in treated and untreated flour was analyzed by χ2 test. Results: The efficacy of a diatomaceous earth (DE) compound (Mitex) as a repellent or an attractant was tested against 9-, 12- and 15-day old larvae of Tribolium castaneum (Herbst). Larvae of all ages were significantly (p<0.001) repelled by DE at doses from 8-32 mg/g food at all exposure periods of 24-, 48-, 72- 96 and 120 h. The mature larvae (15-day old) showed tolerance to the low doses like 2 and 4 mg/g food. Conclusion: The present results revealed that DE can be used as a reduced risk repellent compound in the grain and cereal stores, flour mills and grocery shops to manage the larval population of T. castaneum. Keywords: Age related response; T. castaneum; diatomaceous earth DOI: http://dx.doi.org/10.3329/jbs.v18i0.8773 JBS 2010; 18(0): 40-43